Superfine nano phosphorus-carbon negative electrode material prepared based on in-situ high-temperature phase change in confinement microcavity and preparation method of superfine nano phosphorus-carbon negative electrode material
By conducting high -temperature phase transformation technology in the limited domain micro -cavity, preparing ultra -fine nano -phosphate carbon negative materials, solving the problem of low utilization rate and size of phosphorus in battery applications, and achieve efficient phosphorus use and battery performance promote.
Patent Information
- Application Number
- CN202411432830.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-14
AI Technical Summary
When phosphorus is an anode material for alkali metal ion batteries, it has problems such as low utilization rate and difficult to control in size, which leads to problems such as fast capacity decay, low Coulomb efficiency, and low reversible capacity in battery applications.
Using high -temperature phase transformation technology in the original position of limited domain micro -cavity, by mixing and mixing phosphorus and conductive porous materials in the solvent, mixing and mixing for sand grinding, forming a cover layer with limited domain micro -cavity structure, restricting the range of phosphorus gasification, and in the range of phosphorus gas, and in the range of the range of phosphorus gas, and in it, it is in the range of phosphorus gas, and it is in the range of phosphorus gas. It is restricted. In the transient high temperature device, the phosphorus is sublimated quickly and condensed into ultra -fine nanoparticles.
Improve the use efficiency and conductivity performance of phosphorus, solve the problem of poor volume expansion and electrical conductivity in battery applications, and significantly improve the cycle stability and electrochemical performance of the battery.
Smart Images

Figure CN119349518A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of negative electrode materials for alkali metal ion batteries, and specifically relates to an ultrafine nano-phosphorus-carbon negative electrode material prepared based on in-situ high-temperature phase change in a confined microcavity and a preparation method thereof. Background Art
[0002] As a new type of negative electrode material for alkali metal ion batteries, phosphorus has a very high theoretical capacity (2596mAh / g) and a suitable charging and discharging platform, and has received widespread attention. However, during the charging and discharging process, phosphorus has a high volume expansion rate (>300%) and is easy to pulverize. In addition, it has poor electrical conductivity and is unstable after nano-sizing, which easily leads to problems such as rapid capacity decay, low coulombic efficiency, and low reversible capacity, which limits its application in negative electrode materials for alkali metal batteries. In order to solve the above problems, the current main research direction is to composite it with other matrix materials, and some effective results have been achieved. Other matrices mainly involve carbon-based materials. The high electrical conductivity of carbon-based materials improves the electrical conductivity of the entire electrode. The porous structure of carbon-based materials can buffer the volume expansion of red phosphorus. At the same time, chemical bonds are formed between atoms in the carbon-based materials and red phosphorus to stabilize the structure.
[0003] Commonly used methods are mechanical ball milling and evaporation condensation. The mechanical ball milling method is to accurately weigh the phosphorus source and the carbon source in proportion, put them into a ball mill, add an appropriate amount of ball milling media (milling balls), and seal the tank in an inert atmosphere (such as argon) to prevent oxidation. Then, high-energy ball milling is performed at a set speed and time to fully mix and alloy phosphorus and carbon under the action of mechanical force to form a composite material. Chinese patent application CN202311542975.2 provides a polymer-coated phosphorus-carbon composite material and its preparation method and application. The composite material mainly solves the problems of volume expansion, structural instability, serious electrolyte consumption, poor conductivity, etc. in the prior art phosphorus-carbon composite materials during charging and discharging, especially the problem that the existing process is difficult to achieve uniform coating of materials. However, this method has problems such as uneven mixing, easy agglomeration of fine particles, large energy consumption in the ball milling process, long time, easy to cause oxidation of materials, and increase process complexity and cost. The evaporation condensation method is to heat the phosphorus and carbon sources in a closed container in a vacuum or inert atmosphere to sublimate phosphorus. The sublimated phosphorus gas condenses on the carbon substrate to form a phosphorus layer covering the carbon material. In this method, the phosphorus source is easily condensed on the container wall, the utilization rate is low, and the phosphorus condensed on the carbon substrate is unevenly distributed and difficult to control in size. At the same time, harmful gases are easily generated, which increases safety and environmental protection requirements. Chinese patent application CN202311677198.2 provides a phosphorus-carbon composite negative electrode material and its preparation method and application, which includes using chemical vapor deposition to deposit a phosphorus source on a carbon source to obtain a phosphorus-carbon composite negative electrode material that can be used as a negative electrode material for a sodium ion battery. However, this method has complex process and strict process requirements. In production, parameters such as vacuum, temperature and time need to be strictly controlled, and the equipment cost of chemical vapor deposition is relatively high, which may affect cost-effectiveness in large-scale production. Therefore, a technology that can efficiently utilize the phosphorus source, accurately control the size of phosphorus, and achieve uniform compounding is needed. Summary of the invention
[0004] The purpose of the present invention is to develop a method based on in-situ high-temperature phase change in a confined microcavity to prepare ultrafine nano-phosphorus-carbon negative electrode materials, aiming to solve the problems of low utilization rate and difficult size control during the preparation process of phosphorus as a negative electrode material for alkali metal ion batteries.
[0005] The technical solution adopted by the present invention is as follows:
[0006] A method for preparing ultrafine nano-phosphorus-carbon negative electrode materials based on in-situ high-temperature phase change in a confined microcavity comprises the following steps:
[0007] (1) adding phosphorus and conductive porous material into a solvent, stirring and mixing, and then sand milling, achieving highly uniform mixing and initial size reduction through high-speed rotation and mutual collision of grinding balls;
[0008] (2) reforming and granulating the mixed slurry obtained in step (1) to form solid microparticles, which provide a basis for the subsequent construction of the coating layer;
[0009] (3) coating the particles obtained by reforming and granulating in step (2) to form a coating layer having a confined microcavity structure, wherein the confined microcavity refers to a closed or semi-closed space constructed on the surface of the particles obtained by reforming and granulating by the coating layer, which is used to limit the scope of phosphorus gasification and achieve efficient utilization;
[0010] (4) loading the product obtained in step (3) into the heating zone of a transient high temperature device for transient heating, so that the phosphorus source is rapidly sublimated and evenly diffused in the confined microcavity; instant cooling, the phosphorus vapor is rapidly condensed to form ultrafine nanoparticles, and enters the porous conductive material;
[0011] (5) The product obtained in step (4) is transferred to a sealed container for heat preservation and conversion, and the atmosphere is controlled to reduce the generation of by-products.
[0012] Optionally, the conductive porous material in step (1) is one or more of porous carbon materials, porous metal materials, porous conductive polymers, porous graphene, porous oxide conductive materials, metal organic frameworks, covalent organic frameworks, and carbon-coated porous materials;
[0013] Optionally, the phosphorus source in step (1) is selected from one or more of red phosphorus, black phosphorus, white phosphorus, fiber phosphorus, purple phosphorus, blue phosphorus, green phosphorus, phosphoric acid, phosphate, phosphide, and organic phosphorus, preferably red phosphorus;
[0014] Optionally, the solvent in step (1) is one or more of ethanol, deionized water, isopropanol, propylene glycol methyl ether, N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), ethyl acetate, cyclohexanone, and dichloromethane.
[0015] Optionally, the porous carbon described in step (1) includes: at least one of activated carbon, carbon aerogel, carbon nanotubes, graphene aerogel, ordered mesoporous carbon, activated carbon fiber, porous carbon spheres, and carbonized polymer porous carbon; the porous metal material includes: at least one of foamed aluminum, foamed nickel, foamed copper, porous titanium, porous gold, porous copper, porous magnesium, porous iron, porous cobalt, porous tungsten, porous molybdenum, and porous alloys; the porous conductive polymer includes: at least one of polypyrrole, polyaniline, polythiophene and its derivatives, polythiophene-conductive polymer composites, and conductive polymer-carbon material composites; the porous graphene includes: at least one of three-dimensional graphene aerogel, porous reduced oxide graphene, and porous graphene foam; the porous oxide conductive material includes: porous titanium dioxide, porous tin oxide, porous silicon dioxide, porous iron oxide, porous magnesium oxide, porous oxide At least one of zinc and porous lithium titanate; the metal organic framework includes: at least one of ZIF series, MIL series, NU series, HKUST-1, IRMOF series, UiO series, MOF-5, and PCN series; the covalent organic framework includes at least one of COF-1, COF-5, COF-102, COF-108, TP-COFs, LZU-COF, NUS-COFs, PI-COFs, and TF-COFs; the carbon-coated porous material includes: carbon-coated porous carbon, carbon-coated porous metal material, carbon-coated porous conductive polymer, carbon-coated porous graphene, carbon-coated porous oxide conductive material, carbon-coated metal organic framework, carbon-coated covalent organic framework, carbon-coated porous polymer, carbon-coated porous glass and ceramics, carbon-coated zeolite, and porous carbon-coated bio-based porous material.
[0016] Optionally, in step (1), the mass ratio of phosphorus to the conductive porous material is 1:0.1 to 1:100; the mass ratio of solvent to phosphorus carbon is 1:1 to 1:100; the sand milling speed is 1 r / s to 5000 r / s; the sand milling time is 1 h to 24 h; and the sand milling temperature is 15°C to 100°C.
[0017] Optionally, the reforming granulation method in step (2) includes existing granulation methods such as compression granulation, spray drying granulation, fluidized bed granulation, etc., and the granulation size is 100nm-100μm.
[0018] Optionally, the coating in step (3) includes one or more of a carbon coating, a metal coating, an alloy coating, an oxide coating, a carbide coating, a nitride coating, a polymer coating, a composite coating, and an organic coating.
[0019] Optionally, the coating method in step (3) includes existing coating methods such as chemical vapor deposition, physical vapor deposition, and electrochemical deposition. The key to material design and optimization is to construct a stable microcavity structure through different coating methods to effectively control and utilize phosphorus vapor. Regardless of the coating material or technology used, the core goal is to limit the escape of phosphorus vapor from the inside so that it enters the porous conductive material through capillary force and pressure difference. This process ensures the full utilization of phosphorus vapor, maximizes the utilization rate of phosphorus source, reduces losses and improves material performance.
[0020] Optionally, the coating thickness in step (3) is 0.01 μm-5 μm, and the coating mass ratio to the particle is 1:0.2 to 1:20. The coating thickness design is critical. When the internal phosphorus content is too high and the coating thickness is insufficient, the shell may rupture due to internal gas accumulation and pressure increase, and the structural integrity and performance stability of the material will also be affected, which will not only lead to an increase in specific surface area and more lithium ions being consumed, but also reduce the initial efficiency of the battery. Therefore, when designing the material, it is necessary to select an appropriate coating thickness according to the specific material properties and internal phosphorus content to effectively resist the internal gas pressure and maintain structural integrity, thereby enhancing the stability and life of the battery during cyclic use. In addition, the heating and cooling rates of the material also need to be optimized. Too fast a heating may quickly generate a large amount of internal gas, while the cooling process may cause condensation or volume reduction of the gas. These factors should be considered comprehensively to avoid failure or performance degradation of the material during cyclic use. Through refined coating design and heat treatment process adjustment, the stability and life of the material in practical applications can be ensured. For example, based on experimental data analysis, the minimum coating thickness and optimal heating and cooling rates required under different phosphorus content conditions can be determined to achieve optimal performance. This not only maintains the integrity of the material structure, but also provides higher performance and reliability in applications such as batteries.
[0021] Optionally, the transient heating method in step (4) includes existing transient heating methods such as Joule heating, microwave heating, and plasma heating. During the heating process, a heating method that can achieve rapid heating is usually adopted, and its key advantage is that the material can be quickly heated in a short time and then quickly cooled. This transient cooling is crucial to the formation of the crystal structure of the material because it significantly increases the nucleation rate and shortens the growth time of the crystal, thereby effectively generating nanoscale phosphorus particles. Nanosized phosphorus particles not only help to improve the conductivity of the material, but also significantly improve its overall performance in battery applications, especially cycle stability.
[0022] Optionally, in step (4), the temperature is raised to 350°C to 1000°C by at least one pulse, and the heating rate is 1×10 6℃ / s to 100℃ / s. After reaching the target temperature, the system enters the heat preservation stage. The heat preservation time is 0.01s-200s. After the heat preservation stage, the temperature is immediately lowered to 1×10 6 The temperature is cooled to room temperature at a cooling rate of 100℃ / s to 100℃ / s to form ultrafine nanoparticles. The single pulse time is 0.01s-100s, which refers to the total time from the start of heating to the end of cooling, including heating, insulation and cooling processes. Each pulse operation includes a complete heating-insulation-cooling cycle, with an unlimited number of pulses. The pulse interval is 0.1s-100s, which refers to the time interval between the end of one pulse and the start of the next pulse. During the heating stage, the temperature in the device rises rapidly from the starting temperature to the set target temperature, which is determined according to the experimental requirements. After reaching the target temperature, the system enters the insulation stage, and the temperature remains constant to ensure that the phosphorus source is fully sublimated and diffused. The insulation time can be flexibly adjusted according to the material properties and process requirements to achieve the best effect. After the insulation is completed, the system immediately starts to cool down, and the temperature is quickly reduced to a safe level through rapid cooling, which prompts the phosphorus vapor to condense rapidly and form ultrafine nanoparticles. In the preparation process of battery materials, the heating and cooling rates have a significant effect on crystal nucleation and particle size. Faster heating and cooling rates will cause drastic changes in system temperature, accelerate crystal nucleation, and form smaller crystals due to short growth time. Such small crystals are beneficial to the optimization of the microstructure of the material, making the phosphorus particles more evenly distributed, thereby improving the uniformity and stability of the material, and further enhancing the performance stability of the battery in multiple charge and discharge cycles.
[0023] Optionally, the atmosphere in the heating zone in step (4) is a non-oxidizing atmosphere, including a mixture of one or more gases selected from the group consisting of low vacuum, helium, argon, and nitrogen.
[0024] Optionally, the insulation temperature in step (5) is 100° C. to 400° C., the insulation time is 1 h to 24 h, and the insulation atmosphere is a mixture of one or more gases selected from the group consisting of vacuum, argon, nitrogen, and helium.
[0025] The principle of the present invention is based on in-situ high-temperature phase change in a confined microcavity to prepare ultrafine nano-phosphorus-carbon negative electrode materials, which mainly involves the following key technical steps and mechanisms:
[0026] 1. Construction of confined microcavity structure:
[0027] By constructing a coating layer on the surface of a porous conductive material, a closed or semi-closed microcavity structure is formed. The microcavity structure is used to limit the gasification range and distribution path of phosphorus during the high-temperature phase change process, so as to improve the utilization efficiency and distribution uniformity of phosphorus.
[0028] 2. In-situ high temperature phase change:
[0029] Transient high-temperature technology (such as Joule heat, microwave heating, etc.) is used to rapidly sublimate phosphorus in a confined microcavity and condense it into nanoparticles. By controlling the temperature and the heating and cooling speed, precise size control and uniform distribution of phosphorus can be achieved.
[0030] 3. Use of conductive porous materials:
[0031] Materials with high conductivity and porous structure (such as porous carbon materials, metal organic frameworks, etc.) are selected as the matrix. These materials have the function of adsorbing gasified phosphorus on the one hand, and on the other hand, they can provide a good electron conduction path and physically buffer the volume expansion of phosphorus during the charging and discharging process to avoid material pulverization.
[0032] 4. The role of the coating layer:
[0033] The coating layer (such as carbon layer, oxide layer) constructed on the surface of the material forms a confined microcavity, which enhances the mechanical and chemical stability of the material, inhibits structural rupture caused by the volume change of phosphorus and improves the primary effect.
[0034] 5. Insulation conversion steps:
[0035] The prepared materials are placed in a sealed environment for heat preservation treatment to reduce the generation of by-products.
[0036] The present invention improves the utilization efficiency and conductivity of the material by nano-sizing phosphorus and distributing it evenly in a porous structure, thus solving the problem of volume expansion and poor conductivity of phosphorus in battery applications. The construction of confined microcavities and transient high-temperature phase change technology together achieve precise control of the material structure, thereby improving the cycle stability and electrochemical performance of the electrode material. This innovative method provides new possibilities for the application of phosphorus-based negative electrode materials in sodium ion, lithium ion and potassium ion batteries.
[0037] The method for preparing ultrafine nano-phosphorus-carbon negative electrode materials based on in-situ high-temperature phase change in a confined microcavity proposed in the present invention has the following advantages and outstanding effects compared with the prior art:
[0038] First, through the combination of confined microcavity and high-temperature phase change technology, the structural stability and cycle life of the material are greatly enhanced, and the cycle stability and reversible capacity of the battery are significantly improved. The uniform distribution and high conductivity of the material in the conductive porous structure significantly improve the electrochemical performance of the battery, showing higher energy density and charge and discharge efficiency.
[0039] Secondly, the invention simplifies the material preparation process, using efficient material use and precise size control to reduce production costs and process complexity. This innovative method is applicable to a variety of alkali metal ion batteries, including sodium ion, lithium ion and potassium ion batteries, and broadens the application range of phosphorus-based negative electrode materials.
[0040] In addition, using transient heating technology, phosphorus undergoes rapid phase changes under thermodynamically driven non-steady-state conditions. The coating layer confines the vaporized phosphorus, while the conductive porous material can quickly adsorb the vaporized phosphorus. The nanoparticles formed after transient cooling, combined with the good mechanical properties of the conductive porous material, effectively limit the volume expansion of phosphorus, enhance conductivity, inhibit structural rupture caused by the huge volume change of phosphorus, avoid the loss of active sites, and further improve cycle stability.
[0041] In summary, the present invention overcomes the key problems in traditional technologies through innovative structural design and process improvements, and provides a highly efficient, stable and widely applicable method for preparing phosphorus-carbon negative electrode materials, which demonstrates great potential and advantages in the application of battery technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a scanning electron microscope (SEM) image of the spherical phosphorus-carbon mixed material obtained in Example 1 of the present invention.
[0043] Figure 2 This is the X-ray diffraction (XRD) spectrum of the spherical phosphorus-carbon mixed material particles before and after copper plating in Example 1 of the present invention.
[0044] Figure 3 This is a cross-sectional scanning electron microscope (SEM) image of the spherical phosphorus-carbon mixed material particles of Example 1 of the present invention after copper plating and before Joule heat pulse treatment.
[0045] Figure 4 This is a cross-sectional SEM image of the spherical phosphorus-carbon mixed material particles of Example 1 of the present invention after Joule heat pulse.
[0046] Figure 5 This is a scanning electron microscope (SEM) image of the spherical phosphorus-carbon hybrid material of Example 4 of the present invention after the physical vapor deposition carbon layer.
[0047] Figure 6 The present invention shows a scanning electron microscope (SEM) image of Example 2 showing that the copper shell is not thick enough due to the increase in phosphorus content and the internal pressure is too high, causing the gas to break through the shell.
[0048] Figure 7 The transmission electron microscope (TEM) images of the phosphorus carbon interior at different single pulse times and different temperatures are shown for Example 6 of the present invention.
[0049] Figure 8 This is a cycle performance curve of a button-type battery assembled with spherical phosphorus-carbon mixed material particles before and after Joule heat pulse in Example 1 of the present invention.
[0050] Fig. 9The relationship between the specific capacity (mAh / g) and the cycle number (Cycle Number) of the button-type battery assembled with the spherical phosphorus-carbon mixed material particles of Example 1 of the present invention before and after the Joule heat pulse at different charge and discharge rates (C-rate).
[0051] Fig.10 The figure is a curve showing the relationship between voltage and specific capacity (mAh / g) of a button-type battery assembled with the phosphorus-carbon composite material before and after Joule heat treatment prepared in Example 1 of the present invention during the first charge and discharge process.
[0052] Fig.11 The figure is a comparison of the cycle performance of button-type batteries assembled with the phosphorus-carbon composite material prepared in Example 2 of the present invention before and after Joule heat treatment.
[0053] Fig.12 The cycle performance of a button cell assembled using the phosphorus-carbon composite material after Joule heat treatment obtained in Example 3 of the present invention.
[0054] Fig.13 The relationship curve between voltage and specific capacity (mAh / g) during the first charge and discharge process of button-type batteries assembled with different holding times after the Joule heat pulse prepared in Example 7 of the present invention. DETAILED DESCRIPTION
[0055] The following content appropriately refers to the accompanying drawings to explain in detail and specifically disclose the invention of the present application, which provides a method for preparing ultrafine nano-phosphorus-carbon negative electrode materials based on in-situ high-temperature phase change in a confined microcavity. Certain unnecessary details may be omitted in the description, such as well-known matters and repeated descriptions of the same structure. This is done to avoid the description becoming lengthy so that those skilled in the art can better understand it. In addition, the drawings and the following description are intended to help those skilled in the art fully understand the present application, rather than to limit the subject matter recorded in the claims. Obviously, the described embodiments are only part of the present invention, not all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should also fall within the scope of protection of the present invention.
[0056] If not otherwise specified, all technical features and optional technical features in this application can be combined with each other to form a new technical solution. In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0057] Embodiment 1:
[0058] Mixing preparation: Weigh 50g of red phosphorus and 50g of porous carbon, disperse them in 900g of ethanol, pour them into a sand mill, control the temperature to 25°C, and sand grind at 2000r / s for 2h to obtain a phosphorus-carbon mixed slurry. By controlling the phosphorus-carbon ratio and concentration, the density inside the spray-dried sphere can be regulated. The loose interior can easily lead to the coating entering the interior during subsequent coating; too much red phosphorus and insufficient porous carbon pores can easily lead to condensation and agglomeration of red phosphorus on the surface. In this process, oxidation must be prevented, and uniform mixing must be ensured by adjusting the sand milling speed and time.
[0059] Spray drying: spray drying the mixed slurry, control the gas temperature to 150°C, the gas pressure to 0.2Mpa, and the injection speed to 15rmp to obtain a spherical phosphorus-carbon mixed material. By adjusting the gas pressure and injection speed, the size of the sphere and the uniformity of the coating layer can be controlled. If the size is too large, the coating layer is difficult to be completely coated, and if the size is too small, the thickness of the coating layer is difficult to control.
[0060] Figure 1 :Scanning electron microscope (SEM) images of spherical phosphorus-carbon hybrid materials obtained after spray drying are shown. As can be seen in the figure, the material presents uniform spherical particles, with large particles ranging in diameter from a few microns to more than ten microns, and small particles within a few microns in diameter. The distribution of particles is relatively uniform, and there is no significant aggregation or agglomeration.
[0061] Chemical copper plating: Use chemical copper plating solution to copper plate the spherical phosphorus-carbon mixed material particles. Place 1g of spherical phosphorus-carbon composite material into 50ml of 20g / L stannous chloride sensitization solution and stir for 10min, then soak it in 50ml of 3.8g / L copper salt chemical copper plating solution for 10min, and finally dry it to form a coating layer with a confined microcavity structure, with a thickness controlled at 200nm. This step mainly controls the thickness by controlling the amount of copper plating solution and the copper plating time. If the thickness is too large, it will affect the battery performance, and if the thickness is too small, it will be easily broken by the gas generated after sublimation.
[0062] Figure 2 :Shows the X-ray diffraction (XRD) patterns of spherical phosphorus-carbon hybrid material particles before and after copper plating. In the figure, the horizontal axis represents the 2θ angle and the vertical axis represents the diffraction intensity. There is no significant diffraction peak in the XRD curve of the uncopper-plated material, while the curve after copper plating shows obvious copper crystal characteristic peaks near 43.3° and 50.4°, indicating that the copper plating process was successful.
[0063] Joule heat treatment: Take 0.2g of material and place it in a 5cm long carbon felt. The carbon felt is placed between the open Joule heat positive and negative electrodes in the glove box. The glove box is filled with high-purity argon gas, and the water and oxygen content is less than 0.01ppm. The atmosphere is controlled to ensure that it is not oxidized during the instantaneous heating process. Start the Joule heat device power supply in an atmosphere filled with argon, adjust the current and voltage parameters to voltage: 80V, current: 15A, so that the temperature rises rapidly to 450℃ within 0.1 second, and perform 5 1-second pulse heating to reach the sublimation point of red phosphorus, so that the red phosphorus is vaporized and diffused in the microcavity. After the sublimation process is completed, start the rapid cooling system immediately. Through the rapid circulation of the cooling medium, the temperature in the reaction zone is sharply reduced in an instant. During this process, the phosphorus vapor is quickly condensed to room temperature to form ultrafine nanoparticles, which are effectively embedded in the interior of the porous conductive material. In this step, if the temperature is too high, the internal pressure is large, and it is easy to break through the coating layer; if the temperature is too low, the red phosphorus will not be completely vaporized. By precisely controlling the heating time and temperature, the red phosphorus is evenly distributed, refined to ultrafine nanometer size, and does not agglomerate.
[0064] Figure 3 : Shows a cross-sectional scanning electron microscope (SEM) image of a spherical phosphorus-carbon hybrid material particle after copper plating and before Joule heat treatment. The image shows that the cross-sectional structure of the particle is very dense and has some irregular structural features. The copper plating process forms a dense copper layer on the surface of the material, and the internal structure is relatively uniform.
[0065] Post-treatment: The product obtained in step 4 was sealed and transferred to a tube furnace, argon was introduced, and the temperature was kept at 260° C. for 12 h to ensure that the red phosphorus was completely stabilized.
[0066] Figure 4 :Shows a cross-sectional scanning electron microscope (SEM) image of a spherical phosphorus-carbon hybrid material particle after Joule heat treatment. After treatment, new pore structures are formed inside and on the surface of the material. These pores are caused by the gasification and nano-sizing of red phosphorus. It can be observed from the SEM image that the material structure becomes more complex and the internal pores increase.
[0067] Example 2: The same as Example 1, except that the mass ratio of red phosphorus to porous carbon is 2:1.
[0068] Example 3: Same as Example 1, except that porous graphene is used instead of porous carbon. The high conductivity of graphene can improve the electron transfer efficiency to effectively improve the cycle stability. Example 4: Same as Example 1, except that the carbon coating is manufactured by physical vapor deposition. Physical vapor deposition can achieve precise film thickness control and uniform deposition. The deposited carbon film is pure and has a low impurity content, which helps to improve the electrochemical performance. At the same time, less harmful chemicals are used, and the environmental impact is relatively small.
[0069] Figure 5 : The scanning electron microscope (SEM) image of phosphorus-carbon mixed particles with carbon layers formed by physical vapor deposition is shown. The surface of the carbon layer is smooth and dense, and the shell is complete.
[0070] Example 5: Same as Example 1, except that the copper plating layer thickness is 500nm. With an increase in the copper plating thickness, it can withstand greater internal pressure, is not easy to break, the transient temperature can be higher, and the internal phosphorus content can be increased.
[0071] Figure 6 : The scanning electron microscope (SEM) image shows that the gas breaks through the shell due to insufficient copper shell thickness and excessive internal pressure. Therefore, when designing the material, it is necessary to select the appropriate coating thickness based on the specific material properties and internal phosphorus content to effectively limit the internal phosphorus vapor and maintain the integrity of the shell.
[0072] Example 6: Same as Example 1, except that the single pulse time of the Joule heat treatment is 10 s and the temperature is 500° C. Different temperature and time conditions can adjust the distribution of particles with different particle sizes.
[0073] Figure 7 : Displays transmission electron microscope (TEM) images of the phosphorus carbon interior at different single pulse times and temperatures. The particle size and distribution of the internal phosphorus particles can be controlled by regulating the time and temperature. When the temperature and time are not appropriate, the internal phosphorus particles will aggregate.
[0074] Example 7: Same as Example 1, except that the holding time in the tube furnace is 24 hours. By adjusting the holding time, the by-products are reduced, thereby increasing the overall capacity of the battery.
[0075] Tests and Results
[0076] We selected the phosphorus-carbon composite materials prepared in Examples 1, 2, 3, and 7, assembled them into button cells before and after transient heating treatment, and conducted electrochemical performance tests. In the process of making button cells, a metal lithium sheet was selected as the counter electrode, and the preparation method of the phosphorus-carbon pole piece was as follows: the phosphorus-carbon composite material, the conductive agent SP, and the binder PVDF were uniformly mixed in a mass ratio of 8:1:1, coated on a copper foil, and vacuum dried at 80°C for 12 hours. The dried pole piece was roll-pressed, cut into discs with a diameter of 11 mm, weighed, and placed in a vacuum glove box for button cell assembly.
[0077] The test results of Example 1:
[0078] Figure 8 The cycle performance of button-type batteries assembled using the phosphorus-carbon composite material prepared in Example 1 of the present invention before and after Joule heat treatment is shown.
[0079] The horizontal axis (Cycle Number) indicates the number of cycles of the battery, from 0 to 100 cycles.
[0080] The left vertical axis (Specific Capacity, mAh / g) represents the specific capacity of the battery, in mAh / g, ranging from 0 to 4000mAh / g.
[0081] The right vertical axis (Coulombic Efficiency, Coulombic efficiency %): represents the coulombic efficiency of the battery, in percentage (%), ranging from 0% to 100%.
[0082] The black hollow circles in the figure represent the Coulombic efficiency after Joule heating treatment, and the gray hollow circles represent the Coulombic efficiency before Joule heating treatment.
[0083] The two curves are labeled:
[0084] The black solid dot curve represents the battery performance after Joule heat treatment, showing a significant improvement in the battery specific capacity after heat treatment.
[0085] Gray solid dot curve: represents the battery performance before Joule heat treatment, and its specific capacity is significantly lower than the result after heat treatment.
[0086] It can be seen that the initial specific capacity of the battery is not much different before and after Joule heat treatment, but after multiple cycles, the battery after Joule heat treatment shows a higher capacity retention rate, indicating that the heat treatment process significantly improves the cycle stability of the battery.
[0087] The changing trend of the Coulombic efficiency shows that the Coulombic efficiency after Joule heat treatment is higher than that before Joule heat treatment in the first cycle (the first charge and discharge). However, in long cycles, the Coulombic efficiency of the two is not much different.
[0088] The battery was tested at a current density of 0.26 A / g.
[0089] Fig. 9 The relationship between the specific capacity and the number of cycles of the phosphorus-carbon composite material prepared by Example 1 of the present invention before and after Joule heat treatment at different charge and discharge rates (C-rate) is shown.
[0090] The horizontal axis (Cycle Number) indicates the number of cycles of the battery, ranging from 0 to 70 cycles.
[0091] Vertical axis (Specific Capacity, mAh / g): represents the specific capacity of the battery, in mAh / g, ranging from 0 to 1600mAh / g.
[0092] The curves are labeled:
[0093] Black solid dot curve: represents the battery performance after Joule heating treatment.
[0094] The hollow dot curve represents the battery performance without Joule heat treatment.
[0095] The "0.1C", "0.2C", "0.5C", "1C", and "2C" marked in the figure represent different charge and discharge rates. Usually, C-rate indicates how many times the rated capacity the battery is charged and discharged. For example, 1C means that the charge and discharge are completed within 1 hour. It can be seen that as the C-rate increases, the specific capacity decreases. This is due to the increase in battery polarization and overpotential at high rates. However, the specific capacity of the battery treated with Joule heat at each rate is significantly higher than that of the untreated battery.
[0096] Rate cycling stability: After being tested at different rates, the specific capacity of the battery can still be restored to a high level when it is restored to a low rate (such as 0.1C), especially the battery after Joule heat treatment, which shows good rate cycling stability.
[0097] Comparison of the initial effect before and after Joule heat treatment: Fig.10 The curve showing the relationship between voltage and specific capacity of the phosphorus-carbon composite material prepared in Example 1 of the present invention before and after Joule heat treatment during the first charge and discharge process.
[0098] In the figure:
[0099] Horizontal axis (Specific Capacity, mAh / g): represents the specific capacity of the battery, in mAh / g, ranging from 0 to 3000mAh / g.
[0100] Vertical axis (Voltage, V vs. Li / Li+): represents the voltage of the battery relative to the voltage of lithium / lithium ions, ranging from 0V to 2.5V.
[0101] The two curves are:
[0102] Solid line: represents the voltage-capacity curve of the battery after Joule heat treatment during the first charge and discharge process.
[0103] Dashed line: represents the voltage-capacity curve of the battery during the first charge and discharge process before Joule heat treatment.
[0104] Voltage platform and specific capacity:
[0105] Before Joule heat treatment (dashed line): the battery has unclear voltage platforms at about 1.2V and 0.6V, and the charge specific capacity before treatment is low, at about 1200mAh / g.
[0106] After Joule heat treatment (solid line): After Joule heat treatment, the battery's charge and discharge platform is more obvious, and the charge specific capacity is increased to nearly 1500mAh / g. This shows that heat treatment reduces the particle size of red phosphorus and improves its utilization rate, thereby enhancing its lithium storage capacity and electrochemical activity.
[0107] After Joule heat treatment, the voltage change of the battery during the charge and discharge process is smoother, indicating that the electrochemical reaction of the material is more stable. After heat treatment, the initial specific capacity of the battery increased significantly, showing the positive effect of heat treatment on improving material performance.
[0108] The test results of Example 2:
[0109] Fig.11 The figure shows the comparison of the cycle performance of the phosphorus-carbon composite material before and after the Joule heat treatment prepared by Example 2 of the present invention.
[0110] The horizontal axis (Cycle Number) indicates the number of cycles of the battery, ranging from 0 to 100 cycles.
[0111] The left vertical axis (Specific Capacity, mAh / g): represents the specific capacity of the battery, ranging from 0 to 3000mAh / g.
[0112] The right vertical axis (Coulombic Efficiency, %): represents the coulombic efficiency of the battery, ranging from 0% to 100%.
[0113] The black hollow circles in the figure represent the Coulombic efficiency after Joule heating treatment, and the gray hollow circles represent the Coulombic efficiency before Joule heating treatment.
[0114] The curves in the figure are:
[0115] Black solid dot curve: represents the battery performance after Joule heat treatment.
[0116] Gray hollow dot curve: represents the battery performance before Joule heat treatment.
[0117] Specific capacity change trend:
[0118] After Joule heat treatment: the initial specific capacity of the battery is about 1970 mAh / g. As the number of cycles increases, the specific capacity gradually decreases, and remains at about 1134 mAh / g at the 100th cycle, showing good cycle stability.
[0119] Before Joule heat treatment: The initial specific capacity of the battery is low, about 1800 mAh / g. As the number of cycles increases, the specific capacity decreases significantly, and drops to about 627 mAh / g at the 100th cycle, showing poor cycle performance.
[0120] The changing trend of Coulombic efficiency shows that the first-cycle Coulombic efficiency after Joule heat treatment is higher than that before treatment, but in the long cycle process, the difference between the two is not large.
[0121] Comparison of treatment effects: Compared with Example 1, the initial capacity of the battery in Example 2 has increased, which is due to the increase in phosphorus content. However, too high a phosphorus content will lead to agglomeration in the porous carbon, thereby reducing the utilization rate of phosphorus and causing a decrease in cycle performance. Therefore, it is necessary to achieve the optimal phosphorus content by regulating the pore volume and specific surface area of the porous carbon.
[0122] The test results of Example 3:
[0123] Fig.12 The figure shows the cycle performance of the phosphorus-carbon composite material after Joule heat treatment prepared in Example 3 of the present invention.
[0124] The horizontal axis (Cycle Number) indicates the number of cycles of the battery, ranging from 0 to 50 cycles.
[0125] The left vertical axis (Specific Capacity, mAh / g): represents the specific capacity of the battery, ranging from 0 to 3000mAh / g.
[0126] The right vertical axis (Coulombic Efficiency, %): represents the coulombic efficiency of the battery, ranging from 0% to 100%.
[0127] The grey hollow circles in the figure represent the Coulombic efficiency after Joule heating treatment.
[0128] The black solid dot curve represents the battery performance after Joule heat treatment, showing the stability of battery charging and discharging after heat treatment.
[0129] It can be seen that the use of porous graphene as a porous conductive substrate has better cycle performance, and the cycle retention rate is improved compared with porous carbon as a conductive matrix.
[0130] The battery was tested at a current density of 0.26 A / g.
[0131] The test results of Example 7:
[0132] Comparison of the first-cycle capacity of materials with different insulation time: Fig.13The relationship curve between voltage and specific capacity of the phosphorus-carbon composite material prepared by Example 7 of the present invention with different holding times during the first charge and discharge process is shown.
[0133] Horizontal axis (Specific Capacity, mAh / g): represents the specific capacity of the battery, in mAh / g, ranging from 0 to 3000mAh / g.
[0134] Vertical axis (Voltage, V vs. Li / Li+): represents the voltage of the battery relative to the voltage of lithium / lithium ions, ranging from 0V to 2.5V.
[0135] The two curves are:
[0136] Solid line: represents the voltage-capacity curve of the battery during the first charge and discharge process after 24 hours of insulation.
[0137] Dashed line: represents the voltage-capacity curve of the battery during the first charge and discharge process after 12 hours of insulation.
[0138] It can be seen that the insulation time is conducive to the conversion of more by-products into red phosphorus, increasing the content of red phosphorus, improving the capacity, and reducing the by-products produced during battery cycling.
[0139] In summary, the present invention provides a method for preparing ultrafine nano-phosphorus-carbon negative electrode materials based on in-situ high-temperature phase change in a confined microcavity. The transient temperature rise causes phosphorus to be rapidly vaporized and adsorbed by the porous conductive material, and the microcavity structure limits the vaporized phosphorus to fill the material inside the cavity. After instant condensation, nanoparticles are formed and confined in the pores, which enhances conductivity, provides a buffer for the expansion of phosphorus, effectively inhibits the structural rupture of phosphorus caused by volume change, avoids the loss of active sites, and thus improves cycle stability.
[0140] The above is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any equivalent replacement or change made by any technician familiar with the technical field within the technical scope disclosed by the present invention and based on the technical solution and its conception of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing ultrafine nano-phosphorus-based negative electrode materials based on in-situ high-temperature phase change in a confined microcavity, characterized in that: The following steps are involved: (1) adding phosphorus and conductive porous material into a solvent, stirring and mixing, and then sand milling, achieving highly uniform mixing and initial size reduction through high-speed rotation and mutual collision of grinding balls; (2) reforming and granulating the mixed slurry obtained in step (1) to form solid microparticles, which provide a basis for the subsequent construction of the coating layer; (3) coating the particles obtained by reforming and granulating in step (2) to form a coating layer having a confined microcavity structure, wherein the confined microcavity refers to a closed or semi-closed space constructed on the surface of the particles obtained by reforming and granulating by the coating layer, which is used to limit the scope of phosphorus gasification and achieve efficient utilization; (4) loading the product obtained in step (3) into the heating zone of a transient high temperature device for transient heating, so that the phosphorus source is rapidly sublimated and evenly diffused in the confined microcavity; instant cooling, the phosphorus vapor is rapidly condensed to form ultrafine nanoparticles, and enters the porous conductive material; (5) The product obtained in step (4) is transferred to a sealed container for heat preservation and conversion, and the atmosphere is controlled to reduce the generation of by-products.
2. The method according to claim 1, characterized in that The phosphorus described in step (1) is selected from one or more of red phosphorus, black phosphorus, white phosphorus, fiber phosphorus, purple phosphorus, blue phosphorus, green phosphorus, phosphoric acid, phosphate, phosphide, and organic phosphorus.
3. The method according to claim 1, characterized in that The conductive porous material in step (1) includes one or more of porous carbon materials, porous metal materials, porous conductive polymers, porous graphene, porous oxide conductive materials, metal organic frameworks, covalent organic frameworks and carbon-coated porous materials.
4. The method according to claim 3, characterized in that The porous carbon material in step (1) is selected from at least one of activated carbon, carbon aerogel, carbon nanotube, graphene aerogel, ordered mesoporous carbon, activated carbon fiber, porous carbon sphere, carbonized polymer porous carbon; the porous metal material is selected from at least one of foamed aluminum, foamed nickel, foamed copper, porous titanium, porous gold, porous magnesium, porous iron, porous cobalt, porous tungsten, porous molybdenum, and porous alloy; the porous conductive polymer is selected from at least one of polypyrrole, polyaniline, polythiophene and its derivatives, polythiophene-conductive polymer composites, and conductive polymer-carbon material composites; the porous graphene is selected from at least one of three-dimensional graphene aerogel, porous reduced graphene oxide, and porous graphene foam; the porous oxide conductive material is selected from at least one of porous titanium dioxide, porous tin oxide, porous silicon dioxide, porous iron oxide, porous magnesium oxide, porous zinc oxide, and porous titanate At least one of lithium; the metal organic framework is selected from at least one of the ZIF series, MIL series, NU series, HKUST-1, IRMOF series, UiO series, MOF-5, and PCN series; the covalent organic framework is selected from at least one of COF-1, COF-5, COF-102, COF-108, TP-COFs, LZU-COF, NUS-COFs, PI-COFs, and TF-COFs; the carbon-coated porous material is selected from at least one of carbon-coated porous carbon, carbon-coated porous metal materials, carbon-coated porous conductive polymers, carbon-coated porous graphene, carbon-coated porous oxide conductive materials, carbon-coated metal organic frameworks, carbon-coated covalent organic frameworks, carbon-coated porous polymers, carbon-coated porous glass and ceramics, carbon-coated zeolites, and porous carbon-coated bio-based porous materials.
5. The method according to claim 1, characterized in that The solvent in step (1) is selected from one or more of ethanol, deionized water, isopropanol, propylene glycol methyl ether, NN-dimethylformamide (DMF), N-methylpyrrolidone (NMP), ethyl acetate, cyclohexanone, and dichloromethane.
6. The method according to claim 1, characterized in that The mass ratio of phosphorus to the conductive porous material in step (1) is 1:0.1 to 1:
100.
7. The method according to claim 1, characterized in that The mass ratio of the solvent to the phosphorus carbon in step (1) is 1:1 to 1:
100.
8. The method according to claim 1, characterized in that The sand milling speed in step (1) is 1 r / s to 5000 r / s, the sand milling time is 1 hour to 24 hours, and the sand milling temperature is 15° C. to 100° C.
9. The method according to claim 1, characterized in that: The size of the microparticles in step (2) is 100 nm to 100 μm.
10. The method according to claim 1, characterized in that The coating layer in step (3) is selected from one or more of a carbon coating layer, a metal coating layer, an oxide coating layer, a nitride coating layer, and a polymer coating layer.
11. The method according to claim 10, characterized in that The carbon coating layer in step (3) includes graphene, carbon nanotubes, amorphous carbon, and graphite coating; the metal coating layer includes aluminum, nickel, copper, zinc, titanium, gold, magnesium, iron, tungsten, molybdenum, and alloy coating; the oxide coating layer includes aluminum oxide, titanium oxide, zirconium oxide, silicon oxide, manganese oxide, magnesium oxide, nickel oxide, and cerium oxide coating; the nitride coating layer includes titanium nitride, silicon nitride, aluminum nitride, boron nitride, and zirconium nitride coating; the polymer coating layer includes one or more of polyvinylidene fluoride, polyethyleneimine, polythiophene, polypyrrole, polyaniline, polyacrylonitrile, and polyethylene glycol.
12. The method according to claim 1, characterized in that The thickness of the coating layer in step (3) is 0.01 μm-5 μm, and the mass ratio of the coating layer to the particles is 1:0.2 to 1:
20.
13. The method according to claim 1, characterized in that In step (4), the temperature is raised to 350°C to 1000°C by at least one pulse, and the heating rate is 1×10 6 ℃ / s to 100℃ / s. After reaching the target temperature, the system enters the heat preservation stage. The heat preservation time is 0.01s-200s. After the heat preservation stage, the temperature is immediately lowered to 1×10 6 The temperature is cooled to room temperature at a cooling rate of 100°C / s to form ultrafine nanoparticles.
14. The method according to claim 1, characterized in that The single pulse time is 0.01s-100s, which refers to the total time from the start of heating to the end of cooling, including heating, insulation and cooling processes. Each pulse operation includes a complete heating-insulation-cooling cycle. The number of pulses is not limited. The pulse interval is 0.1s-100s, which refers to the time interval from the end of one pulse to the start of the next pulse.
15. The method according to claim 1, characterized in that The atmosphere in the heating zone in step (4) is a non-oxidizing atmosphere, a low vacuum, or a mixture of one or more of helium, argon, and nitrogen.
16. The method according to claim 1, characterized in that The insulation temperature in step (5) is 100° C. to 400° C., the insulation time is 1 hour to 24 hours, and the insulation atmosphere is a mixture of one or more gases selected from the group consisting of vacuum, helium, argon, and nitrogen.
17. A method for preparing ultrafine nano-phosphorus-based negative electrode materials based on in-situ high-temperature phase change in a confined microcavity, characterized in that: Prepared according to the method according to any one of claims 1 to 16.
Citation Information
Patent Citations
Polymer-coated phosphorus-carbon composite material as well as preparation method and application thereof
CN117476896A
Phosphorus-carbon composite negative electrode material and preparation method and application thereof
CN117673304A
Preparation method of lithium ion battery cathode material
CN103296261A
Phosphorus-based negative electrode material and preparation method thereof, negative electrode and lithium ion battery
CN109216682A
Negative electrode active material and preparation and application thereof
CN111785946A
Cited By
Lithium ion battery electrode material and preparation method thereof
CN121260767A
Phosphorus-based alloy composite negative electrode material and application thereof in all-solid-state secondary battery
CN121331805A
Ultra-fine nanophosphorus-carbon negative electrode material prepared on basis of in-situ high-temperature phase change in confined microcavities, and preparation method therefor
WO2026082054A1